2018
DOI: 10.1080/14636778.2018.1549982
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid UCB banks in China – public storage as ethical biocapital

Abstract: In China, under the heading of "private-for-public" banking, hybrid UCB banking has been politically supported by the government and is based on regulation developed since the 1990s. Although hybrid UCB banking was regarded as an 'ethical' alternative to private UCB banking due to its accessibility to 'the people', this study, based on archival research and interviews with bankers, medical professionals, scientists and pregnant women contends that the practice of this ideal needs to be closely scrutinized. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In China, public–private integration banks are politically supported by the government. The aim was to cope with funding shortages in an ethically acceptable way [ 45 ]. Despite that, it can be observed that cord blood stocked in private banks exceeds the number of publicly stored units in every bank in China.…”
Section: Umbilical Cord Blood Bankingmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, public–private integration banks are politically supported by the government. The aim was to cope with funding shortages in an ethically acceptable way [ 45 ]. Despite that, it can be observed that cord blood stocked in private banks exceeds the number of publicly stored units in every bank in China.…”
Section: Umbilical Cord Blood Bankingmentioning
confidence: 99%
“…This might be a result of the parents` strong belief that their child’s cord blood could be of personal use in the future. To curb this trend, it has been proposed to define an appropriate ratio of public to private storage for UCB banks [ 45 ].…”
Section: Umbilical Cord Blood Bankingmentioning
confidence: 99%